2015
DOI: 10.1190/geo2015-0032.1
|View full text |Cite
|
Sign up to set email alerts
|

Differential evolution-based optimization procedure for automatic estimation of the common-reflection surface traveltime parameters

Abstract: The common-reflection surface (CRS) method is a sophisticated alternative to the traditional common-midpoint stacking because its traveltime approximation allows for the use of more traces than the normal moveout. This in turn requires more parameters for the moveout description, thus increasing the computational burden of the parameter estimation. In the literature, a suboptimal strategy is often used, which decreases the complexity but, as we found in this work, compromises the accuracy of the parameters in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
16

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 29 publications
1
46
0
16
Order By: Relevance
“…As is done for the ZO CRS method, this search strategy is referred to as sequential CO CRS search (Barros et al . ).…”
Section: Common‐offset Common‐reflection‐surface Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…As is done for the ZO CRS method, this search strategy is referred to as sequential CO CRS search (Barros et al . ).…”
Section: Common‐offset Common‐reflection‐surface Methodsmentioning
confidence: 97%
“…; Barros et al . ), where it was shown that the joint estimation of the CRS variables generates better results than those from the sequence of one‐variable searches at the expense of higher computational costs. Barros et al .…”
Section: Global Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Parameter estimation is performed by the heuristic algorithm differential evolution (DE) based on the same strategy made by Barros et al . (). The stretch‐free parameter is estimated by an exhaustive search, considering 2Ntrueprefixmax+1 semblance computations for each time sample.…”
Section: Resultsmentioning
confidence: 97%
“…1 brute-force approach, but they are not guaranteed to find the global optimum. The most popular are simulated annealing (Müller, 2003;Garabito et al, 2012;Minato et al, 2012) and differential evolution (Barros et al, 2015).…”
Section: Introductionmentioning
confidence: 99%